Stability of the Financial System and the Seciurity of the Polish System Deposit Guarantee - Kropacz, Izabela (Journal of Finance and Financial Law, 2017)
The aim of the elaboration was to presentations tasks of the Banking Guarantee Fund and to present the scope of protection, principles and mode of implementation of guarantee and financing its activities. Activities of the Bank Guarantee Fund is highly significant for the economy, the banking system, banks and their customers. All banks are obligated to belong to the system, which increases the stability of the entire financial system. Depositors entrusting your money to financial institutions should take special care and control institutions, whether it is supervised by the Polish Financial Supervision Authority and whether their funds are covered by the scheme of deposits guarantee because it is a determinant of financial security. Done an assessment of the safety of funds entrusted to financial market institutions in Poland. Indicated institutions securing deposited funds. At a well-functioning financial market can be the basis a development and economic growth, and the effective functioning of supervisors reduces the risk of bank activity. The collected data is presented in graphs.